Influence Of Family Hypertension On Blood Pressure, Serum Cholesterol, High Density Lipoprotein Cholesterol In General Population - BHENDE A.M; ZADE S.B; SITRE S.R (International Journal of Pharma and Bio Sciences, 2012)
An elevated arterial pressure is probably the most important public health problem now a days. In addition to number of environmental factors e.g. obesity, occupation, alcohol intake etc., genetic factors also have long been assumed to be important in the genesis of hypertension. Many workers have also shown co-relation of hyperlipidemia with early hypertensive heart disease in young individuals. The cases were divided into two groups - I and II consisting of 50 case in each group. Each group was further divided into two sub groups Ia and Ib , IIa, and IIb, having 25 cases in each group., Cases of group Ib and IIb were children of hypertensive parents. Whereas cases of Ia and IIa belong to children of healthy parents with negative family history of hypertension. The present study has been planned to evaluate blood pressure, serum cholesterol, high density lipoprotein cholesterol, on one hundred cases in community. The results of these study show that serum cholesterol, serum cholesterol/ HDLC ratio were significantly high and HDLC was significantly low in cases of Ib and IIb as compared to Ia and IIa groups respectively, indicating that the cases having positive family history of hypertension are more prone to suffer from high blood pressure and hyperlipidemia as compared to those having negative family history of hypertension. Health professionals should therefore utilize every opportunity to include direct family members in health education.